THE IDIOM PUZZLE: UNRAVELING THE SYNTAX AND SEMANTICS OF IDIOMATIC EXPRESSIONS - Khadjieva D.T; Kokanova N. J. (Journals Park Publishing, 2023)
Idiomatic expressions play a vital role in human language, adding depth, richness, and cultural nuances to communication. These phrases often consist of combinations of words whose meanings cannot be inferred from their individual components. Unraveling the syntax and semantics of idiomatic expressions presents a fascinating puzzle for linguists and cognitive scientists. This article explores the nature of idiomatic expressions, investigates their syntactic and semantic characteristics, and highlights the challenges in deciphering their meaning. By shedding light on the intricacies of idiomatic language, we aim to enhance our understanding of human cognition and language processing.
Keywords: Idiomatic expressions, Syntax, Semantics, Compositionality, Figurative language, Cultural variations, Cognitive processing, Ambiguity, Transparency, Contextual cues